Factors That Affect Doctors To Reach Patients To The Regional Hospital Eduardo Ximenes Baucau. Timor Leste - Filipe De Neri Machado (Journal for Quality in Public Health, 2020)
In the current condition, referral cases to third-level health services for cases that should have been completed at third-level services are still quite high. If the patient has complications, severity of illness, the presence of other chronic diseases that are difficult and patients with decreased immune system, all of whom need further treatment, the primary care physician must promptly and accurately make a judgment and decide to do it reference. The purpose of this study was to explore the factors influencing physicians to refer patients to Regional Hospital Eduardo Ximenes Baucau. Timor Leste. The design of this study is a qualitative study with a phenomenological approach with the focus of the research directed to explore factors that influence doctors to refer patients to Regional Hospital Eduardo Ximenes Baucau. Timor Leste with a sample of 15 informants taken by purposive sampling technique. The findings show that the patient referral system from the Community Health Center to Reffrel Hospital starts when the patient arrives then the doctor will check whether or not to be referred. Criteria that become the doctor's hand in making a referral when referring a patient have the hand criteria namely the patient's condition and facilities. The role of the Medical Team is to make a decision before referring patients. Standard Operating Procedure (SOP) for patient referral. There are special services for patients, especially veteran patients, diplomats, and public figures. To refer a patient to another health facility the doctor must see whether the patient's condition is included in the referral criteria or not. In addition, a doctor must also look at health facilities. If the facilities are inadequate, the doctor can make a patient referral. In addition there are drug and HR criteria. That is, doctors need to pay attention to the stock of drugs they have. Then HR (Human Resources) in this case is a specialist doctor